O projeto estadual de reforma agrária e o caso do assentamento Carlos Marighella - Santa Maria -RS: entre o ideal e o possível - Rodrigues, Marli (2010)
This paper aims to analyze the state agrarian reform proposal through land reform policy of the Olívio Dutra s government (1999-2002), as well as recovering the main issues concerning implementation, development and destiny of the Carlos Marighella settlement. The proposal of this government that maintained a strong opposition to land reform policy from Fernando Henrique Cardoso s federal government (1999-2002), which prioritizes the market land reform policy, through the land credit policy entitled Bank of the Land. During his election campaign, the state government pledged to settle ten thousand families across the state agrarian reform policy, thus came out the Carlos Marighella settlement in the city of Santa Maria-RS in the year of two thousand, aiming at forming a differential settlement in the shape of an agricultural production cooperative, using collective work, without private ownership of land and developing productive activities based on agroecology. So because of these characteristics this settlement should be "model" for others to be implemented in the state of Rio Grande do Sul. Methodologically this study fits in a qualitative research, that used as method, a case study; concerning the research instruments was used: a) a bibliographic and documentary research for the historical recovery achievement about agrarian reform in Brazil, and in particular the FHC s proposal for agrarian reform in Brazil, and the Olívio Dutra s agrarian reform proposal in the state of Rio Grande do Sul; b) semi structured interviews applied to key informers that originates the empirical discussion, being, therefore, primary sources datas. These informers were divided in three groups (state government, municipal government/institutions, technical advisory body). Through the contributions from social actors interviewed, it concludes there was an improvement in the agrarian reform from agrarian reform state policy on analyzed, although state government haven t been achieved the goal of settling ten thousand families. It is also stressed that the Carlos Marighella settlement, despite of being recognized in the whole country and in the world as well by its particular characteristics of its implementation, underwent a break in the original project. Concerning this failure of the settlement in question, the main causes were, the lack of collective conscience on behalf of the settlers, non-existent of a technical advisory body prepared to work with agroecology and the difficulty of the settlers in overcoming the inherent conflicts to human nature.